2017
DOI: 10.1016/j.jopan.2015.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Ease of Care From a Patients' Perspective Comparing Fentanyl Iontophoretic Transdermal System Versus Morphine Intravenous Patient-Controlled Analgesia in Postoperative Pain Management

Abstract: In this meta-analysis, fentanyl ITS is associated with some advantages in terms of an EOC profile from a patients' perspective when compared with morphine IV PCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…improved confidence/comfort with the device, dosing, and knowledge/understanding) and less technical issues associated with autonomous administration. Although the transdermal route of delivery has been notorious for inconsistencies in medication delivery/absorption it appears as though transdermal Fentanyl produces results in terms of pain control and patient satisfaction which are on par with morphine [16]. Additionally, studies have also demonstrated that it has an improved side effect profile and has less frequent adverse events associated with its use, including hypotension, hypoventilation, nausea, vomiting, pruritus and tachycardia [17].…”
Section: Fentanylmentioning
confidence: 99%
“…improved confidence/comfort with the device, dosing, and knowledge/understanding) and less technical issues associated with autonomous administration. Although the transdermal route of delivery has been notorious for inconsistencies in medication delivery/absorption it appears as though transdermal Fentanyl produces results in terms of pain control and patient satisfaction which are on par with morphine [16]. Additionally, studies have also demonstrated that it has an improved side effect profile and has less frequent adverse events associated with its use, including hypotension, hypoventilation, nausea, vomiting, pruritus and tachycardia [17].…”
Section: Fentanylmentioning
confidence: 99%
“…[7][8][9][10][11] The most commonly used opioid analgesic in patientcontrolled intravenous analgesia (PCIA) is sufentanil; 11 however, it's the adverse reactions associated with this drug are serious, and studies have shown that it inhibits immune function. 10,12,13 As a new potent synthetic opioid analgesic, dezocine is mostly used for moderate to severe analgesia. It is characterised by complete activation of the κ receptor, spinal cord analgesia, mild sedation and respiratory depression.…”
Section: Introductionmentioning
confidence: 99%